Estudo comparativo da placa em ponte associada ao pino intramedular e da placa de compressão dinâmica na fixação de osteotomia experimental em fêmur de coelhos (Oryctolagus cuniculus). Análises clínica, radiográfica, histológica e cintilográfica - Natalie Ferreira Borges (2011)
The objectives were to benchmark and monitor the fracture healing of femoral osteotomy in rabbits after fixation with dynamic compression plate and bridge plate associated with intramedullary pin. Were used 14 New Zealand rabbits, four months old with mean weight of 3.5 pounds, from the Experimental Farm Professor Hélio Barbosa's Veterinary School of UFMG. The animals were randomly divided into two groups (I and II). All rabbits underwent osteotomy across the middle third of right femur. In the group I was made to fix the osteotomy with the bridge plate (BP) associated with intramedullary pin, introduced the technique of minimal invasion. In group II, we used dynamic compression plate (DCP) via the conventional approach. Both groups were evaluated clinical, radiographic, histologic and scintigraphic findings. Clinical assessments were performed weekly until the 12th postoperative week and radiographic examinations were performed before, immediately after, at 15, 30, 45, 60 and 90 days. The bone scintigraphy were performed before and at 20, 50 and 90 days after surgery to monitor the bone metabolism qualitatively and quantitatively. Observed perfusion and bone healing process. After 90 days of study, there was histopathologic evaluation of the osteotomized area and the insertion of screws. In the region of the osteotomy was observed predominance of trabecular bone in group I and group II, the predominance of bone osteons, compatible with the original bone. On insertion of the screws did not differ between groups and there was cortical discontinuity, little necrosis and local hemorrhage. The two types of fixation have led to consolidation within the scheduled period, maturing in early fixation with DCP fixation compared with BP. Scintigraphy demonstrated by the indices of activity and image characteristics, the process of bone healing was significantly greater in animals undergoing early fixation with DCP.